Association between the phenotype of metabolically healthy obesity and the risk of myocardial infarction. (25th November 2020) - Malyutina, S; Mustafina, S; Vinter, D; Rymar, O; Shcherbakova, L; Verevkin, E.U; Gafarov, V; Bobak, M
Abstract: Aim: This study aimed to investigate the associations between the metabolically healthy obesity (MHO) and the risk of myocardial infarction (MI) in a Russian population sample. Materials and methods: A random population sample of men and women aged 45–69 years old at baseline was examined in 2003–2005 in a Russian city; after that the cohort was followed-up for 12 years on the average (2003–2016). A sub-cohort of subjects with body mass index (BMI) ≥30 kg/m 2 at baseline was selected for present study (3157 individuals, 73.2% women); of those, 3008 subjects free from baseline history of MI/acute CHD was included for analysis. The data on incident myocardial infarction (MI) were ascertained from register of MI, two repeated examinations and repeated postal interviews during 12-year follow-up of the cohort. We used two definitions of MHO: by NCEP ATPIII, 2001 (the presence of 2 or less components of the metabolic syndrome) and by IDF 2005 (waist circumference (WC) ≥94 cm in men and ≥80 cm in women regardless of risk factors). Multivariable Cox regression was conducted using the SPSS package (V. 13.0). Results: The prevalence of MHO at baseline ranged from 20% (by IDF) to 45% (by NCEPATPIII) in obese sub-cohort. Among subjects with MHO at baseline, about one half of subjects developed metabolically unhealthy obesity phenotype (MUO) during 12-years. Women were more likely to retain MHO (32%) and more frequent transited from MUO to MHO (14%) compared to men (22% and 6% by IDF criteria, correspondently) during 12 years. The relative risk of incident MI in subjects with MUO at baseline was 1.9 times higher than in those with MHO (HR 1.9, 95% CI 1.2–2.9) by NCEPATP III. Among men, the relative risk of MI in those with MUO (by NCEP ATP III) was 2 times higher than in a group with MHO (HR 2.1, 95% CI 1.1–4.0). Among women, the relative risk of MI in those with MUO (by NCEP ATP III) was 2.2 (95% CI 1.2- 4.2) compared to MHO group. Using the IDF criteria, the relative risk of MI in MUO vs. MHO was 2.2 (95% CI 0.9–5.7) in men and 2.2 (95% CI: 0.9–5.7) in women. Conclusions: In this study population, men aged 45–69 have more frequent progression from metabolically healthy to metabolically unhealthy obesity during 12 years compared to women. The 12-year risk of incident MI in subjects with MUO was approximately twice higher compared to MHO and the excess risk was similar in men and women. Funding Acknowledgement: Type of funding source: Public grant(s) – EU funding. Main funding source(s): Wellcom Trust